Interplay between ALK2R206H mutant receptor and autophagy signaling regulates receptor stability and its chondrogenic functions - Laura Coculo; Marius Wits; Irene Mariani; Giulia Fianco; Serena Cappato; Renata Bocciardi; Nicoletta Pedemonte; Elisabetta Volpe; Serena Ciolfi; Rosario Luigi Sessa; Serena Rinaldo; Francesca Cutruzzolà; et al. (Cell Death Discovery)
Abstract Heterozygous mutations in the Bone morphogenetic protein (BMP) type I receptor ACVR1, encoding activin-like kinase 2 (ALK2), underlie all cases of the rare genetic musculoskeletal disorder Fibrodysplasia Ossificans Progressiva (FOP). The most commonly found mutant ALK2 p.R206H receptor variant exhibits loss of auto inhibition of BMP signaling and can be activated by Activins, while wild-type receptors remain unresponsive. Consequently, the downstream chondrogenic signaling is enhanced, thus driving heterotopic ossification within soft connective tissues. Despite several investigational treatments being evaluated in clinical trials, no cure for FOP exists today. The cellular and molecular mechanisms underlying disease progression are still being deciphered. In this study, we show a close interplay between the mutant ALK2R206H receptor signaling and dysregulation of the autophagic flux triggered by hypoxia. Mechanistically, reduced autophagic flux correlates with increased stability of ALK2R206H, resulting in sustained signaling. Of note, we demonstrated that Rapamycin, under clinical investigation as a treatment for FOP, inhibits chondrogenic differentiation in an autophagy-dependent manner. Consistently, other pharmacological autophagy inducers, like Spermidine, can reduce ALK2R206H driven chondrogenic differentiation in vitro. These results were verified in FOP patient-derived cells. In conclusion, this study shows that aberrant autophagic flux mediates sustained ALK2R206H signaling, introducing a novel druggable target in FOP by reactivating autophagy.